THE INFLUENCE OF TREFFINGER LEARNING MODELS ON MATHEMATICS COMMUNICATION SKILLS OF STUDENTS - Salingkat, Suhartini; Bilalu, Anastasia (Jurnal Pendidikan Matematika dan IPA, 2021)
This study aims to analyze the impact of the Treffinger learning model on students' mathematical communication skills. This research was conducted at Senior High School 1 Bulagi grade 10th, 2018/2019 academic year. This type of research was a Quasi-Experimental study with a Pretest-Posttest Control Group Design. Data collection on mathematical communication skills used test instruments. The results revealed that the mathematical communication skills of students taught using the Treffinger learning model were higher than those taught using the Student Team Achievement Division / STAD cooperative learning model (FCount = 5.78> Ftable = 4.03). It can be seen from the results of the research that application of the Treffinger learning model has a higher effect on students' communication skills compared to the Student Learning Achievement Division (STAD) cooperative learning model. It is proven from the average mathematical communication skills of students taught with the Treffinger learning model on the written text indicator, drawing and mathematical expression expressed at 50.67 while the students taught with the Student Team Achievement Division (STAD) cooperative learning model on the written indicator text, drawing and mathematical expressions were stated at 47.50.